The Influence of Audit Standard Compliance and Going Concern on Audit Opinions - Farra Ayu Bestari; Herman Ruslim (Eduvest - Journal of Universal Studies, 2025)
The aim of this research is to examine the effects of following auditing standards and going concern criteria on audit views in consumer non-cyclical companies listed on the Indonesia Stock Exchange for the years 2021–2023. 327 businesses' secondary data is used in this quantitative research. The research sample comprised 264 companies, and the sampling technique employed was purposive sampling based on certain criteria. The data was analyzed using logistic regression and descriptive statistical analysis methods in SPSS software version 26. The results demonstrate that liquidity and solvency factors have a positive and significant impact on the going concern audit opinion, whereas activity indicators have no effect. The factors influencing going concern audit opinions are clarified by this study, particularly in relation to Indonesian consumer non-cyclical enterprises.